2015
DOI: 10.1016/j.brat.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain acceptance incrementally predicts disability in polytrauma-exposed veterans at baseline and 1-year follow-up

Abstract: War veterans are at increased risk for chronic pain and co-occurring neurobehavioral problems, including posttraumatic stress disorder (PTSD), depression, alcohol-related problems, and mild traumatic brain injury (mTBI). Each condition is associated with disability, particularly when co-occurring. Pain acceptance is a strong predictor of lower levels of disability in chronic pain. This study examined whether acceptance of pain predicted current and future disability beyond the effects of these co-occurring con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 61 publications
(80 reference statements)
3
13
0
Order By: Relevance
“…These results are consistent with those of recent studies that have evaluated pain-related acceptance as a protective psychological variable in trauma-exposed people with chronic pain [6,33,34] and shown that acceptance (the opposite of experiential avoidance) is related to fewer psychological symptoms and better outcomes after traumatic exposure [67].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results are consistent with those of recent studies that have evaluated pain-related acceptance as a protective psychological variable in trauma-exposed people with chronic pain [6,33,34] and shown that acceptance (the opposite of experiential avoidance) is related to fewer psychological symptoms and better outcomes after traumatic exposure [67].…”
Section: Discussionsupporting
confidence: 92%
“…Second, consistent with a small body of literature looking at psychological flexibility, PTSD, and chronic pain [6,[32][33][34], participants with PTSD reported lower levels of pain-related acceptance and committed action as well as higher levels of cognitive fusion compared to those without PTSD. No significant difference between these two groups was seen on values-based action.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…For instance, in 2015 research, chronic face, head, and neck pain were significantly related to depression among war veterans living with PTSD [108]. It is critical to study these variables within war veteran populations, given that they are at high risk for chronic pain and related neuro-behavioral problems [109]. This is also the case for other vulnerable populations that are particularly at risk for PTSD such as traumatized refugees [85].…”
Section: Discussionmentioning
confidence: 99%